Analisis Kurikulum Pembelajaran Mata Pelajaran Pendidikan Agama Islam Kelas Program Khusus Di SMP Muhammadiyah 1 Surakarta - Seta, Auzan Jiwangga; Shohib, Muhammad Wildan (Cetta: Jurnal Ilmu Pendidikan, 2025)
This research aims to analyze the Islamic education learning curriculum at the Muhammadiyah 1 Surakarta education level in the special program class. This research uses a qualitative descriptive method to identify and evaluate the structure, content and implementation of the current Islamic education curriculum. The results of this research are the Islamic education subject curriculum in the special program class at SMP Muhammadiyah 1 Surakarta using the independent learning curriculum learning method. Islamic education subjects have an important role in shaping student character, introducing the values of the Islamic Religion, and preparing them to live according to the teachings of the Islamic Religion.